Overcoming the requirement of semantic equivalence: a case of morphological variation studied with variability’s spaces concept - Samamé Rispa, Anahís (2018)
From the field of sociolinguistics, this research studies a case of morphological variation, the use of imperfect and pluperfect subjunctive of Spanish (-ra/-se), through the concept of variability’s spaces postulated by Caravedo (1991, 2014), wich overcames the sociolinguistic variable’s requirement of semantic equivalence. The sample is formed by 54 Spanish speakers born in Lima with university education. The phenomenon is investigated in order to determine if the variant -ra is displacing the variant -se. In the same way, it is intended to know if the choice of one form or another is statistically conditioned by the verbal tense. It is concluded that the use of -ra exceeds the use of -se in the sample studied. Likewise, verbal tense was shown as a statistically significant variable: simple tense is related to the use of -ra and compound tense, with -se.